Characterization of recombinant UDP- and ADP-glucose pyrophosphorylases and glycogen synthase to elucidate glucose-1-phosphate partitioning into oligo- and polysaccharides in streptomyces coelicolor - Asención Diez, Matías Damián (2012)
Streptomyces coelicolor exhibits a major secondary metabolism, deriving important amounts of glucose to synthesize pigmented antibiotics. Understanding the pathways occurring in the bacterium with respect to synthesis of oligo- and polysaccharides is of relevance to determine a plausible scenario for the partitioning of glucose-1-phosphate into different metabolic fates. We report the molecular cloning of the genes coding for UDP- and ADP-glucose pyrophosphorylases as well as for glycogen synthase from genomic DNA of S. coelicolor A3(2). Each gene was heterologously expressed in Escherichia coli cells to produce and purify to electrophoretic homogeneity the respective enzymes. UDP-glucose pyrophosphorylase (UDP-Glc PPase) was characterized as a dimer exhibiting a relatively high V max in catalyzing UDP-glucose synthesis (270 units/mg) and with respect to dTDP-glucose (94 units/mg). ADP-glucose pyrophosphorylase (ADP-Glc PPase) was found to be tetrameric in structure and specific in utilizing ATP as a substrate, reaching similar activities in the directions of ADP-glucose synthesis or pyrophosphorolysis (V max of 0.15 and 0.27 units/mg, respectively). Glycogen synthase was arranged as a dimer and exhibited specificity in the use of ADP-glucose to elongate α-1,4-glucan chains in the polysaccharide. ADP-Glc PPase was the only of the three enzymes exhibiting sensitivity to allosteric regulation by different metabolites. Mannose-6-phosphate, phosphoenolpyruvate, fructose-6-phosphate, and glucose-6-phosphate behaved as major activators, whereas NADPH was a main inhibitor of ADP-Glc PPase. The results support a metabolic picture where glycogen synthesis occurs via ADP-glucose in S. coelicolor, with the pathway being strictly regulated in connection with other routes involved with oligo- and polysaccharides, as well as with antibiotic synthesis in the bacterium.